Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Manajerial Pada RSUD Wilayah Bogor - Riyani S. Saputri; Sri Hartoyo; Hendro Sasongko (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
This study aims to determine and analyze the role of participation in budgeting on managerial performance whereas in this study there is a moderating variable that is Reward in the BLUD RSUD Bogor region. The data obtained were processed using Microsoft Excel 2018 and Eviews. The sampling technique with purposive sampling technique. The results obtained after a study of 85 respondents using multiple linear regression analysis models explained that there is an influence of participation in budgeting on managerial performance. Budgeting can act as a planning and performance criteria, where the budget can be used as a control system to measure managerial performance. This means that participatory budgeting can be assessed as a managerial approach that can improve the performance of each manager as an individual, and reward does not affect managerial performance. Continue to evaluate the performance using the Balanced Scorecard seen from the main performance indicators and achieve performance for the realization of performance achievements included in the predicate is very good in 2017-2018.